EXISTENCE OF STRONG M-BASES IN NONSEPARABLE BANACH SPACES (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
In the paper the important question on existence of strong M-bases is considered. A new kind resolution of identity is introduced. Based on this resolution, necessary and sufficient conditions for existence of strong M-bases are determined. As a consequence, the existence of strong M-bases in certain Banach spaces is shown.